Potential of Pectin in Lemon’s and Bali Orange’s Peel as Antidislipidemia and Antioxidant in Hypercholesterolemia Rats (Rattus novergicus) - Noer Kumala Indahsari; Aristanto Aristanto; Rio Rio (Fakultas Kedokteran Universitas Lambung Mangkurat, 2020)
Abstract: Dyslipidemia is a lipid metabolism disorder characterized by an increase or decrease in plasma lipid fractions. Lemon’s and Bali Orange’s Peels, which are usually discarded, can be used because they contain pectin compounds. The presence of pectin compounds contained in the Lemon and Bali oranges Peels is expected to potentially reduce the risk factors for cardiovascular disease. This research method was conducted with pure experimental, namely One Group Pre-Test-Post Test Design. With 5 groups of white rats, the first was a positive control group which was only given normal food, the second was a negative control group which was given hypercholesterolemia and the third group was the treatment group who were given Lemon orange peel extract 10%, Bali orange peels extract 10% and a mixture Lemon and Bali orange peel extract 10%. The results of this study were obtained that the administration of Lemon orange peel ethanol extract and Balinese orange peel can effectively reduce total cholesterol levels, from 181.87 mg / dL to 69.29 mg / dL, down around 61.91%, HDL levels are almost the same, levels LDL decreased from 56.76 mg / dL to 45.71 mg / dl, meaning around 19.47%, Triglyceride levels decreased from 192.50 mg / dL to 77.83 mg / dL, which was around 59.57%, levels MDA decreased from 8.19 mg / dL to 6.37 mg / dL, which is down about 22.22% in white rats (Rattus novergicus) made hypercholesteroalmia. Ethanol extract of Lemon and Bali orangse peels containing pectin can effectively reduce total cholesterol, LDL, HDL, Trygliceryde, and Malodialdehyd (MDA) Levels Keywords: Hypercholesterolamia, Pectin, Antidislipidemia, and Antioxidant